POTENSI MATEMATIKA DI PENDIDIKAN DASAR PADA TRADISI BETUKAH MASYARAKAT SUKU DAYAK DAN MELAYU SELIMBAU - Margawati, Maria; Yusmin, Edy; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to describe society activity, mathematics content in Primary Education, and construct learning scenario of Betukah Tradition. The subject of this research are three people work as penjaja? from Dayak Tribe, three people work as penjaja? from Malay Tribe, a teacher from Dayak Tribe, and a teacher from Malay Tribe. The result and data analyze from subjects are (1) Society activity on Betukah Tradition consist of three steps, there are preparation step, process step, and final step; (2) Mathematics content on preparation step in Betukah Tradition are Sets in Grade, Numbers in Grade, Weight Measurement in Grade, Measurement in Grade, Plane in Grade, Identifying Characteristik of Plane in Grade, Circle in Grade, and Curved Face of Three Dimensional Objects in Grade. Mathematics content on process step in Betukah Tradition are Measurement in Grade, Direct Proportion in Grade, and Mathematics Operation of Multiplication and Division in Grade. Mathematics content on final step in Betukah Tradition is Measurement in Grade; (3) To construct learning scenario of mathematics learning that consist of Betukah Tradition need to collect literature of Betukah Tradition. Keywords: Betukah Tradition, Dayak Tribe, Malay Tribe